Error Analysis of Grammatical Errors in Junior High School Students’ Recount Text Writing - Nelu Sahidah; Andrian Nuriza Johan; Juita Triana (Dinasti Research, 2026)
Writing in English is a crucial ability in the modern, globalized society. English, one of the most popular languages in the world, is essential for communication, commerce, education, and technology. Writing well in English enables people to communicate with people from another country, share information, and clearly convey ideas. For EFL (English Foreign Language) learners, mastering English grammar is still a major issue, especially in settings where English is not used for daily communication. This study looks at grammatical error and most common grammatical errors in the recount texts written by SMP VIP Asy-Syafi’iyyah Purworejo students. This study differs from previous studies by focusing on a pesantren-based school context. The research employed a descriptive qualitative method in analyzing the errors based on Burt, Dulay, and Krashen on Surface Strategy Taxonomy. The data sources of this research are the recount texts created by 18 seventh-grade students of SMP VIP Asy-Syafi’iyyah Purworejo. The results of this research found 242 grammatical errors: omission (19%), addition (9%), misformation (69%), and misordering (3%) Misformation was the most dominant error. The finding suggests that English teachers in pesantren-based schools should focus more on verb tense instruction to mitigate misunderstanding in written English communication.